2014
DOI: 10.1021/jf500357x
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Dilution Gas Chromatography–Mass Spectrometry for Quantification of Thymoquinone in Black Cumin Seed Oil

Abstract: Black cumin seed (Nigella sativa L.) is a widely used spice and herb, where thymoquinone (2-isopropyl-5-methyl-1,4-benzoquinone) is the major bioactive compound. Here, a stable isotope dilution (SID) gas chromatography-mass spectrometry (GC-MS) technique was developed for the quantification of thymoquinone. A doubly deuterated thymoquinone ([(2)H2]-thymoquinone) was synthesized for the first time with more than 93% deuteration degree shown by mass spectrometry and proton nuclear magnetic resonance ((1)H NMR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…Generally, the seeds have been reported to contain many potentially important components in the matrices, but the major and most desired compounds in BSO are thymoquinone, dithymoquinone, thymohydroquinone, and thymol (Figures 3(a)–3(d)), owing to the conformational flexibility feature [29]. Earlier studies documented the existence of these components via chromatography-mass spectrometry analysis [30, 31]. In this study, the green-colored arrow in Figure 3 exhibits the desired bond that can undergo free rotation without a considerable energy cost, making the compounds very flexible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the seeds have been reported to contain many potentially important components in the matrices, but the major and most desired compounds in BSO are thymoquinone, dithymoquinone, thymohydroquinone, and thymol (Figures 3(a)–3(d)), owing to the conformational flexibility feature [29]. Earlier studies documented the existence of these components via chromatography-mass spectrometry analysis [30, 31]. In this study, the green-colored arrow in Figure 3 exhibits the desired bond that can undergo free rotation without a considerable energy cost, making the compounds very flexible.…”
Section: Resultsmentioning
confidence: 99%
“…Previously conducted research studies showed that thymoquinone is a major bioactive constituent of BSO. For this reason, different techniques have been used in the past to identify and quantify the thymoquinone compound in BSO, such as high-performance liquid chromatography (HPLC) [37], pulse polarography [38], differential pulse voltammetry [39], thin-layer chromatography [27], and gas chromatography-mass spectrometry (GC/MS) [30].…”
Section: Resultsmentioning
confidence: 99%
“…5 Furthermore, MAPK signaling cascades are activated by a variety of growth factors involved in kinds of biological responses, such as the production of cytokine and cell death. 8 Black cumin seed oil has been used as a traditional medicine of a range of diseases for a long history, such as diabetes, hypertension, inammation, gastrointestinal disturbances, and cancer. 7 Thymoquinone (TQ), a bioactive natural product obtained from the black cumin seeds of Nigella sativa Linn, is a widely used spice or herb throughout India and the Middle East.…”
Section: Introductionmentioning
confidence: 99%
“…bei dessen Anteil im Öl je nach geografischer Herkunft der Pflanze stark schwankt [5,15,20,25,31]. Das Extraktionsverfahren beeinflusst den Gehalt an Thymochinon ebenfalls erheblich [25].…”
Section: Axel Brattströmunclassified